1975
DOI: 10.1172/jci107920
|View full text |Cite
|
Sign up to set email alerts
|

Detection of platelet isoantibodies by (3H)serotonin platelet release and its clinical application to the problem of platelet matching.

Abstract: A B S T R A C T The detection of platelet isoantibodies by the release of ['H]serotonin from platelets has been evaluated. The conditions for optimal release of ['H]serotonin with platelet isoantibodies using a microtechnique have been defined. A group of cardiac surgery patients were followed pre-and post-transfusions, with 48% developing a positive serotonin release assay. Of these patients, 16% also had a platelet complement-fixing and/or lymphocytotoxic isoantibody. There was variation in the degree of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1976
1976
1980
1980

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…Yet, production of HLA lymphocytotoxic antibodies after platelet transfusions has not been systematically studied. In addition, other types of antibodies that can be detected with platelet aggregometry (9)(10)(11) and platelet serotonin release techniques (12,13) have not been simultaneously compared. To characterize the antibody response to human isologous platelet transfusion, we conducted a systmatic transfusion study in nine platelet recipients who had severe bone marrow hypoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, production of HLA lymphocytotoxic antibodies after platelet transfusions has not been systematically studied. In addition, other types of antibodies that can be detected with platelet aggregometry (9)(10)(11) and platelet serotonin release techniques (12,13) have not been simultaneously compared. To characterize the antibody response to human isologous platelet transfusion, we conducted a systmatic transfusion study in nine platelet recipients who had severe bone marrow hypoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other authors [6,9] have demonstrated that not only the inhibition of uptake, but also the release fo 14C-serotonin of platelets is induc ed by alloantibodies. Therefore, this test was recommended for the detection and characterization of platelet alloantibodies [10] and for platelet matching in transfu sion therapy [6], If a generally accepted serological tech nique such as platelet MCF is to be substitut ed or supplemented by other tests, certain prerequisites ought to be fulfilled: sensitivity, reproducibility and simplicity.…”
Section: Inhibition Of Uc-serotonin Uptakementioning
confidence: 98%
“…The relative insensitivity of these methods, however, has prompted the search for addi tional tests. Recently, two methods have been introduced in platelet immunology, the antibody-induced inhibition of 14C-serotonin uptake and I4C-serotonin release [1,4,6,9,10]. It has been claimed that these techni ques are not only more sensitive than the usual serological methods [6,10], but are also suitable for the detection of platelet…”
mentioning
confidence: 99%
“…In recent years, methods for determining anti-platelet antibodies have been devel oped, which include assays for platelet fac tor 3 [16,[19][20][21]26], 14C-serotonin release [10,15,17,18,25], immunofluorescent anti body test [4-7, 10, 27], platelet migration inhibition [13,23] and 125I-labeled protein A the advantage that the method is relatively simple.…”
Section: Introductionmentioning
confidence: 99%